National culture and earnings management in emerging markets: The role of IFRS mandatory adoption - Viana, D. B. C., Jr.; Lourenço, I.; Ohlson, M. P.; Lima, G. (International Journal of Managerial and Financial Accounting, 2023)
This study investigates the association between national culture and earnings management in emerging markets and analyzes the role of International Financial Reporting Standards (IFRS) mandatory adoption in dampening the influence of national culture on earnings management. Based on a sample of 12,209 firm-year observations from 14 emerging markets, and using several proxies for both accrual-based earnings management (AEM) and real earnings management (REM), we provide empirical evidence that firms from countries with higher levels of uncertainty avoidance, power distance, and long-term orientation, and firms from countries with lower levels of indulgence and masculinity, are associated with higher levels of earnings management. Furthermore, the empirical findings suggest that the IFRS mandatory adoption (associated with a better financial reporting system) moderates the association between cultural factors and earnings management by dampening the influence of national culture on either AEM or REM.